2014
DOI: 10.5005/jp-journals-10033-1209
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy for Morbid Obesity: Robotic vs Standard Laparoscopic Sleeve Gastrectomy Methods

Abstract: Aim:The aim of this study is to compare robotic laparoscopic sleeve gastrectomy with standard laparoscopic sleeve gastrectomy done for morbid obesity with regards to operative time and short-term patient outcome in a developing world.Background: Excision of the fundus and greater curvature of the stomach in sleeve gastrectomy not only restrict intake but also reduces the level of ghrelin in the circulating blood. Obesity surgery has benefited from the advent of surgical robot with its celebrated advantages (en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Robotic surgery performed with ELS is generally referred to as an advanced surgical technique for multiple types of procedures, including gastric bypass [ 10 12 , 28 ], sleeve gastrectomy [ 12 15 ], liver resection [ 18 , 19 , 30 , 31 ], colorectal surgery [ 20 24 , 32 – 34 ], thoracic surgery [ 25 ], nephrectomy [ 26 , 35 ], pancreatectomy [ 27 ], bladder surgery [ 34 ], and prostate surgery [ 36 ]. These procedures typically take longer than laparoscopic or open surgery [ 10 , 11 , 13 , 14 , 18 ], but have comparable or lower complication rates and/or more favorable perioperative outcomes [ 11 14 , 25 , 27 , 36 ]. In these studies, stapling was typically performed by an assistant laparoscopic surgeon, and it was generally reported that although technically demanding, surgical procedures performed with the da Vinci robotic system or ELS are practical and safe.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Robotic surgery performed with ELS is generally referred to as an advanced surgical technique for multiple types of procedures, including gastric bypass [ 10 12 , 28 ], sleeve gastrectomy [ 12 15 ], liver resection [ 18 , 19 , 30 , 31 ], colorectal surgery [ 20 24 , 32 – 34 ], thoracic surgery [ 25 ], nephrectomy [ 26 , 35 ], pancreatectomy [ 27 ], bladder surgery [ 34 ], and prostate surgery [ 36 ]. These procedures typically take longer than laparoscopic or open surgery [ 10 , 11 , 13 , 14 , 18 ], but have comparable or lower complication rates and/or more favorable perioperative outcomes [ 11 14 , 25 , 27 , 36 ]. In these studies, stapling was typically performed by an assistant laparoscopic surgeon, and it was generally reported that although technically demanding, surgical procedures performed with the da Vinci robotic system or ELS are practical and safe.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%